Very low-frequency electrical spectroscopy analysis of an ovine renal tissue - Faezeh Azimi Pirsoltan; Mohammad Reza Karafi (Discover Applied Sciences)
Abstract This study investigates three main regions of a sheep's kidney: the cortex, outer medulla, and inner medulla. The research introduces an impedance measurement setup designed to assess the electrical characteristics at ultra-low frequencies (below 0.1 Hz), capturing both the real and imaginary components of electrical permittivity and conductivity. The apparatus can evaluate the electrical attributes of samples from the kidney's three specified regions, each measuring 20 mm × 10 mm × 1.5 mm. Parameters such as admittance, electrical permittivity, electrical conductivity, and power factor are determined through mathematical formulas. The primary objective of this study is to address the gaps in low-frequency dielectric property data of kidney tissue, specifically focusing on the energy absorption characteristics of different regions of sheep’s kidney. Findings suggest that these parameters display a pronounced peak at ultra-low frequencies (below 30 mHz). This peak, consistent across various tests, is evident in the graphs representing the imaginary part of the conductivity and the phase of admittance. It signifies a frequency at which the tissue stores a higher amount of electrical energy throughout the tested frequency spectrum. Such characteristic could be pivotal for tissue characterization, diagnostic processes, and therapeutic strategies.